2022
DOI: 10.1007/978-3-031-14740-1_13
|View full text |Cite
|
Sign up to set email alerts
|

HSP70-HSP90 Chaperone Networking in Protein-Misfolding Disease

Abstract: Molecular chaperones and their associated co-chaperones are essential in health and disease as they are key facilitators of protein folding, quality control and function. In particular, the heat shock protein (HSP) 70 and HSP90 molecular chaperone networks have been associated with neurodegenerative diseases caused by aberrant protein folding. The pathogenesis of these disorders usually includes the formation of deposits of misfolded, aggregated protein. HSP70 and HSP90, plus their co-chaperones, have been rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 268 publications
0
4
0
Order By: Relevance
“…Formation of this Hsp70-HOP-Hsp90 complex is critical for the activity of the Hsp70-Hsp90 chaperone cycle and correct folding of client proteins. While Hsp70 alone can efficiently fold some substrates, it arrests the folding of other clients due to the highly hydrophobic nature of its substrate-binding chamber [ 98 , 100 ]. To complete their folding, these clients must be transferred from Hsp70 to Hsp90, which highlights the orchestrated activity of these two essential cytoplasmic chaperones.…”
Section: Stip1/hop Proteinmentioning
confidence: 99%
“…Formation of this Hsp70-HOP-Hsp90 complex is critical for the activity of the Hsp70-Hsp90 chaperone cycle and correct folding of client proteins. While Hsp70 alone can efficiently fold some substrates, it arrests the folding of other clients due to the highly hydrophobic nature of its substrate-binding chamber [ 98 , 100 ]. To complete their folding, these clients must be transferred from Hsp70 to Hsp90, which highlights the orchestrated activity of these two essential cytoplasmic chaperones.…”
Section: Stip1/hop Proteinmentioning
confidence: 99%
“…Disaggregation and degradation of Aβ 1–40 /Aβ 1–42 and p-Tau proteins are induced by several HSPs [ 28 ]. It has been observed that these proteins are refolded by HSP70 and HSP90, which promote their solubility, induce their breakdown through the proteasome system, and reduce their synthesis [ 35 , 153 , 154 , 155 ]. Moreover, HSC70, HSP90, and HSP70 coordinate to regulate the polymerization of Tau, preventing its clustering [ 28 , 156 , 157 ].…”
Section: Heat Shock Proteins (Hsps) and Epsmentioning
confidence: 99%
“…The neuroprotective effects of HSF1 as exemplified above can be attributed to the induction and action of a number of molecular chaperones. In this regard, HSP70 and HSP90 are the members of the chaperone family that are analyzed most and whose neuroprotective activity is understood best [69]. Chaperones counteract the toxicity of aggregates using at least three mechanisms: (1) preventing amyloid formation, (2) disaggregating misfolded proteins, and (3) sequestering aggregates to specialized subcellular structures [54].…”
Section: Heat Shock Response and Neuroprotectionmentioning
confidence: 99%